Fashions in Literature - Warner, Charles Dudley, 1829-1900 (Salt Lake City, UT : Project Gutenberg, 2004)
"Fashions in Literature" by Charles Dudley Warner is a critical examination of literary trends and tastes, written in the late 19th century. This work is characterized as a collection of essays exploring how literary fashions evolve, drawing parallels with changing social customs, particularly in dress. Warner engages with the idea of beauty and utility in literature, reflecting on the ephemeral nature of popular tastes and the enduring qualities that define great literature. In this collection, Warner articulates the various influences that shape public taste in literature over time, comparing the fleeting nature of literary trends to the capriciousness of fashion in clothing. He discusses how many works that momentarily capture public imagination often lack lasting value, likening them to garments that quickly go out of style. Warner also emphasizes the importance of clarity, psychological realism, and personal charm as the hallmark qualities of enduring literature. By scrutinizing contemporary writers and their reception, he encourages readers to seek out works that convey deep human knowledge and artistic integrity, rather than merely following the latest fads in literary expression. Ultimately, Warner advocates for a discerning approach to literature, one that prioritizes substance over the ephemeral allure of novelty. (This is an automatically generated summary.)
Release date is 2004-12-05
Produced by David Widger
Keywords: Literature